Effectiveness of plyometric or blood flow restriction training on technical kick force in taekwondo - Ayşe Hazal Boyanmiş; Manolya Akin (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2022)
Introduction. The aim of this study was to understand the effect of blood flow restriction (BFR) and plyometric training methods on the development of taekwondo technical kick force in active taekwondo athletes. Material and Method. 31 taekwondo athletes, aged between 15 and 18 years, voluntarily participated in the study. They were divided into the blood flow restriction, plyom-etric training and control groups. In addition to taekwondo training, blood flow restriction and plyometric training group were trained for 6 weeks. Technical strike force measurements were made with Herman Digital Trainer, placed on the Hasedo. The difference was examined by the paired sample t-test. Comparison of three groups was made with a use of the Friedman test. Re-sults. Statistically significant pre- and post-test differences were found in all technical impact strength values except Tolyochagi right leg in groups participating in BFR training. The difference in the right and left foot and palding kick, the right foot tolyochagi kick, and the right-left foot dwitchagi stroke was statistically significant only in the BFR training group. Conclusions. Con-sidering the effective development of the BFR method on technical strike force in Taekwondo athletes, it is thought that adding the BFR method to routine taekwondo training under the su-pervision of an expert will positively contribute to success.